2001
DOI: 10.1002/ijc.10181
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type I expression in experimental anaplastic thyroid carcinoma: Regulation and relevance for tumorigenicity

Abstract: Fibrosis in solid malignancies plays a significant role in tumor pathophysiology. Potential mechanisms for collagen type I deposition in anaplastic thyroid carcinoma (ATC) were investigated using 6 characterized ATC cell lines. Three of these cell lines, which produced collagen type I, had, as a group, a poor tumorigenicity when inoculated in athymic mice. This group of cells generated tumors in 4 of 24 injected animals (17%). Pro-␣1(I) collagen mRNA-expressing carcinoma and stromal cells were interdispersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Induced genes included MMPs (MMP3, -10, -12, -13) (38). Another category of genes that was greatly overexpressed in transformed PC cells were those encoding adhesion/structure-associated proteins, such as collagen 1 (Col1α1), thymosin β4, and galectin-3, previously reported to be overexpressed in thyroid carcinomas (39)(40)(41)(42). The dual-specificity phosphatase (DUSP6) was also previously identified as a gene upregulated in human PTC samples (41).…”
Section: Function Of the Genes Modulated By Ret/ptc3 Hras(v12) And Bmentioning
confidence: 99%
“…Induced genes included MMPs (MMP3, -10, -12, -13) (38). Another category of genes that was greatly overexpressed in transformed PC cells were those encoding adhesion/structure-associated proteins, such as collagen 1 (Col1α1), thymosin β4, and galectin-3, previously reported to be overexpressed in thyroid carcinomas (39)(40)(41)(42). The dual-specificity phosphatase (DUSP6) was also previously identified as a gene upregulated in human PTC samples (41).…”
Section: Function Of the Genes Modulated By Ret/ptc3 Hras(v12) And Bmentioning
confidence: 99%
“…Direct comparisons between Thena and these cell lines would be more ideal to conclude these results. The in vivo growth of Thena cells was comparable to other established anaplastic thyroid carcinoma cell lines (Dahlman et al 2002). Nevertheless, none of the published thyroid carcinoma cell lines have been reported to induce cancer cachexia in nude mice.…”
Section: Discussionmentioning
confidence: 56%
“…Although the difference might influence the survival data of each group, some untreatable reasons, like multiple liver metastasis, distant metastasis or sever hepatic dysfunction, might be correlated with recurrences in COL1A1 down-regulated cases. In connection with this result, Dahlman et al [32] reported that there was a tendency toward a negative correlation between the ability to produce collagen type I and tumorigenicity in the xenograft mouse model of anaplastic thyroid cancer cell lines. This is because collagen type I-producing cancer cells separate themselves from surrounding stromal components that are essential for tumor growth.…”
Section: Discussionmentioning
confidence: 87%